PENERAPAN MODEL PEMBELAJARAN MARKET PLACE ACTIVITY BERBANTUAN INTERNET DALAM MENINGKATKAN HASIL BELAJAR PAI KELAS VIII SMPN 3 LEMBANG KAB. PINRANG - Irwan Irwan (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
This article discusses about application of learning model of Internet-based place market place in improving result of learning process of Islamic Religion Class VIII SMPN 3 Lembang Pinrang District. This study aims to determine the learning outcomes before and after the implementation of learning model Internet Place Activity assisted the internet, and whether there is an increase in learning results of Islamic Religious Education. This type of research includes experimental research, as it seeks to obtain objective, valid, and reliable data using numerical data, preferably pretest and posttest learning, observation and documentation. Data obtained through observation, tests, and documentation. The results of this study indicate, (1) The result of student learning process before the treatment (pretest) application of learning model of Market Place Activity assisted Internet, obtained mean (mean) equal to 64,12. (2) The result of student learning process after treatment (posttest)) application of learning model of Internet Place Activity with Internet, obtained mean (mean) equal to 87,64. And the improvement of the learning outcomes in the implementation of the Class VIII Classroom Internet Activity Learning model at SMPN 3 Lembang shows a significant improvement. Based on the research that has been done will give the impact of a better learning process. Some of the implications in this research as a form of learning process development that the teacher expected should be able to implement the Active, Innovative, Creative, Effective and Exciting Learning Model on teaching and learning activities by using methods and varied classroom settings and using modules, So it can lead to student motivation in learning.